The Clinical Utility of the Seated Wall Angel as a Test with Scoring - Chad Kofoed; Allison Palmsten; Jonathon Diercks; Michael Obermeier; Marc Tompkins; Terese L Chmielewski (International Journal of Sports Physical Therapy)
# Background